The 1960s Drought and the Subsequent Shift to a Wetter Climate in the Catskill Mountains Region of the New York City Watershed ... - Seager, Richard; Kushnir, Yochanan; Pederson, Neil; Nakamura, Jennifer A.; Jurburg, Stephanie Denisse (Columbia University, 2012)
The precipitation history over the last century in the Catskill Mountains region that supplies water to New York City is studied. A severe drought occurred in the early to mid-1960s followed by a wet period that continues. Interannual variability of precipitation in the region is related to patterns of atmospheric circulation variability in the midlatitude east Pacific–North America–west Atlantic sector with no link to the tropics. Associated SST variations in the Atlantic are consistent with being forced by the anomalous atmospheric flow rather than being causal. In winter and spring the 1960s drought was associated with a low pressure anomaly over the midlatitude North Atlantic Ocean and northerly subsiding flow over the greater Catskills region that would likely suppress precipitation. The cold SSTs offshore during the drought are consistent with atmospheric forcing of the ocean. The subsequent wet period was associated with high pressure anomalies over the Atlantic Ocean and ascending southerly flow over ...